Effects of exenatide on microvascular reactivity in patients with type 2 diabetes and coronary artery disease: A randomized controlled study. (23rd November 2020) - Östlund Papadogeorgos, Nikolaos; Kuhl, Jeanette; Shore, Angela; Kahan, Thomas; Jörneskog, Gun; Kalani, Majid
Abstract: Objective: We studied the effect of the GLP‐1RA exenatide on skin microvascular function in patients with T2DM and CAD. Methods: Thirty‐five patients with T2DM, CAD, and HbA1C 42–86 mmol/mol were randomized to treatment with exenatide or conventional non‐GLP‐1‐based therapy for 12 weeks. Skin microvascular function was examined in the forearm by LDF and iontophoretic application of acetyl choline and SNP, and by PORH at baseline and after 12 weeks. Blood samples for fasting plasma glucose, HbA1C, and lipid profile were collected. Results: At 12 weeks, patients on exenatide showed reductions in HbA1C (from 63.5 ± 13 to 60.7 ± 14 mmol/mol, p  = .065), body weight (from 92.6 ± 16 to 89 ± 16 kg, p  < .001), and systolic blood pressure (from 141 ± 13 to 134 ± 16 mm Hg, p  < .05) as compared to the conventionally treated group. There were no significant changes in skin microvascular function between or within the two groups at follow‐up. Conclusions: Three months' daily treatment with the GLP‐1RA exenatide in T2DM patients with CAD showed no significant effects on skin microvascular function or blood glucose control, while this study confirms a reduction in body weight and blood pressure by exenatide, as compared to conventional antidiabetic drug treatment.